Cognitive Auditory Evoked Potential in children with speech sound disorder (Research, Society and Development, 2020)
To analyze whether speech sound disorder influences P300 latency and amplitude in children. Cross-sectional, quantitative, prospective study. The sample was divided into two groups: group with typical speech development and group with speech sound disorder. The study was divided into the stages of sample recruitment, speech assessments and P300 assessment. Appropriate statistical tests were used. The group of children with speech sound disorder had significantly higher responses to the variable latency when compared to the group with typical speech development. Phonological disorder influenced P300 latency in children with disorganization or inadequate phonological system.